2017
DOI: 10.1021/acs.jpcb.7b09698
|View full text |Cite
|
Sign up to set email alerts
|

Combined TD-DFT-SOS-CIS(D) Study of BOPHY Derivatives with Potential Application in Biosensing

Abstract: A set of 13 bis(difluoroboron)-1,2-bis((pyrrol-2-yl)methylene)hydrazine (BOPHY) dyes is studied through a hybrid time-dependent density functional theory (TD-DFT)-scaled opposite spin-configuration interaction singles with a double correction [SOS-CIS(D)] approach accounting for solvent effects, to shed light onto the structure-property relationships of these recently developed chromophores. In the first step, we calculate the absorption-fluorescence crossing points with refined TD-DFT models considering the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 64 publications
0
28
0
Order By: Relevance
“…This gives access to BOPHY derivatives absorbing in the far-red region. Theoretical studies have described [9] how various substituents located at different sites on the BOPHY core interact to push the absorption transitions towards lower energy. Intersystem-crossing to the corresponding triplet-excited state, which is ineffective for the parent compound, can be promoted by incorporation of iodine atoms in the central BOPHY core [10].…”
Section: Introductionmentioning
confidence: 99%
“…This gives access to BOPHY derivatives absorbing in the far-red region. Theoretical studies have described [9] how various substituents located at different sites on the BOPHY core interact to push the absorption transitions towards lower energy. Intersystem-crossing to the corresponding triplet-excited state, which is ineffective for the parent compound, can be promoted by incorporation of iodine atoms in the central BOPHY core [10].…”
Section: Introductionmentioning
confidence: 99%
“…In order to visualize the electron-density redistribution during the HOMO → LUMO transition, electron density difference plots (EDD) were employed ( Fig. 6), 91 3-thiophene ring during the transition is larger than that of the 5-thiophene ring, indicating that introduction of the thiophene donor at the 3 position in dye 2 is more effective than that at the 5 position in 3. Accordingly, 3-thiophene dye 2 has a higher-lying HOMO than stereoisomer 3, which is consistent with the CV data.…”
Section: Theoretical Analysismentioning
confidence: 99%
“…It was found that SFPCIS is capable of qualitatively reproducing conical intersections and general potential energy surface characteristics, as computed using full configuration-interaction (FCI). Chibani et al 47,48 and Ponce-Vargas et al 49 have applied SOS-CIS(D) to large, highly π-conjugated boron containing dyes. In these three studies, SOS-CIS(D) energies are used to correct overestimated TD-DFT excitation energies, while keeping several key features that are better captured by TD-DFT; e.g.…”
Section: Absorption and Emission Spectramentioning
confidence: 99%